Method for recycling primary aggregate by using solid construction waste
Through the steps of crushing, magnetic screening, water soaking, stirring and screening of solid construction waste, the problem of uneven quality of recycling aggregates caused by complex components of construction waste is solved, and efficient recycling and preparation of uniform and stable recycled aggregates are achieved.
Patent Information
- Application Number
- CN202510130613.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-30
- Publication Date
- 2025-04-25
AI Technical Summary
The complex composition of construction waste leads to uneven quality of recycling aggregates, affecting the quality and use effect of building materials.
By crushing solid construction waste into 1mm-3mm pieces, removing metal from magnetic screen, soaking and stirring in water, screening and grinding, aggregate particles with a particle size of 0.16mm were obtained, and screened through a 100 mesh vibrating screen to obtain recycled regenerated native aggregate.
It realizes efficient recycling of solid construction waste, prepares recycled aggregates with uniform and stable quality, and improves the use effect and economic benefits of building materials.
Smart Images

Figure CN119874239A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the recycling of solid construction waste, and in particular to a method for recycling primary aggregates using solid construction waste. Background Art
[0002] With the continuous development of society, on the one hand, the volume of civil and commercial buildings has grown rapidly, and the consumption of building materials has gradually increased. Large-scale mining of building materials, such as mining natural sand and gravel in nature, will destroy green vegetation, expose raw ore, destroy natural landscapes, cause soil erosion, and even seriously damage the ecological environment. On the other hand, civil and commercial buildings generate a large amount of construction waste during the construction, maintenance and demolition process. It is estimated that during the construction of every 10,000 square meters of new buildings, about 500 to 600 tons of construction waste are generated, and the demolition of 10,000 square meters of old buildings will generate about 7,000 to 12,000 tons of construction waste. Construction waste itself is a building material, which can be used as raw materials for the production of engineering materials.
[0003] Therefore, the recycling and reuse of construction waste has aroused people's interest. In fact, many companies have begun to try to use recycled construction waste to prepare aggregates and use them to prepare recycled and renewable virgin aggregates.
[0004] However, the composition of construction waste or building debris is complex, mostly including coarse aggregate, fine aggregate, micro powder and brick-concrete powder. If these components cannot be separated and treated separately, various materials will be mixed together, which will not only affect the quality of recycled aggregates, but also lead to poor quality and lack of uniformity of building materials made from different batches of aggregates. Summary of the invention
[0005] The main advantage of the present invention is to provide a method for recycling primary aggregates by using solid construction waste, which can utilize the recycled solid construction waste to prepare recycled aggregates with uniform and stable quality.
[0006] Other objects and features of the present invention will be fully reflected in the following detailed description.
[0007] According to one aspect of the present invention, a method for recycling raw aggregates from solid construction waste that can achieve the aforementioned objectives and other objectives and advantages comprises the following steps:
[0008] Step 1: Crush the solid construction waste into recycling fragments with a diameter of 1mm-3mm, and separate them through a 6-15 mesh sieve;
[0009] Step 2: Using a magnetic screen to remove the iron-containing metal pieces in the garbage recycling fragments to obtain primary recycling garbage fragments;
[0010] Step 3: Soak the primary recycling waste fragments in water for at least 1 hour;
[0011] Step 4: Soak the soaked primary recycling waste pieces in water and stir for at least 5 minutes;
[0012] Step 5: pouring the fully stirred primary recycled garbage fragments onto a 7-16 mesh screen and washing them with water to obtain secondary recycled garbage fragments; and
[0013] Step 6: Grind the secondary recycled waste fragments to grind them into aggregate particles with a particle size of 0.16 mm, and screen the ground aggregate particles through a 100-mesh vibrating screen to obtain recycled and regenerated primary aggregate, wherein the solid construction waste comes from the walls of the building.
[0014] Further objects and advantages of the present invention will be fully apparent from an understanding of the following description and the accompanying drawings.
[0015] These and other objects, features and advantages of the present invention will be more fully understood from the following detailed description and accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 2 is a schematic diagram of the structure of recycled primary aggregate according to the above embodiment of the present invention.
[0017] Figure 2 It is a flow chart of a method for recycling raw aggregates using solid construction waste according to the above embodiment of the present invention.
[0018] Figure 3 It is a diffraction image of recycled primary aggregate with different particle sizes recycled from construction waste according to the above embodiment of the present invention. DETAILED DESCRIPTION
[0019] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art can think of other obvious variations. The basic principles of the present invention defined in the following description can be applied to other embodiments, variations, improvements, equivalents, and other technical solutions that do not deviate from the spirit and scope of the present invention.
[0020] Those skilled in the art should understand that, in the disclosure of the present invention, the terms "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, which are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. Therefore, the above terms should not be understood as limiting the present invention.
[0021] It is to be understood that the term "one" should be understood as "at least one" or "one or more", that is, in one embodiment, the number of an element may be one, while in another embodiment, the number of the elements may be multiple, and the term "one" should not be understood as a limitation on the quantity.
[0022] Reference to the attached drawings of the specification Figure 1 and Figure 2 As shown, according to an embodiment of the present invention, the raw material used in the method of recycling primary aggregates from solid construction waste is solid construction waste. There are various types of construction waste or building waste, and the components of different construction wastes are obviously different. The solid construction waste used to recycle aggregates in this article comes from the walls of buildings. The main components of the walls of buildings are aggregates, steel fragments, brick-concrete powder, etc., with a high aggregate content and few component types, so the aggregates are easier to separate. When recycling primary aggregates from construction waste, it is necessary to first remove the useless or even harmful components in the construction waste in order to separate the primary coarse aggregate and fine aggregate in the construction waste.
[0023] In this article, the present invention effectively separates aggregates from construction waste in the following manner. First, a crusher or a pulverizer is used to crush the construction waste into 6-15 mesh (particle diameter is approximately corresponding to 1mm-3mm) garbage recycling fragments, and sieves and separates to remove small particles and dust in the garbage recycling fragments. In the process of crushing the construction waste, components with a larger hardness (hardness of 5-7) in the construction waste, such as stones and gravel, are more likely to form garbage recycling fragments with a preset diameter of 1mm-3mm (approximately corresponding to a 6-15 mesh sieve) when crushed, and components with a smaller hardness (hardness of 2.5-3.5) in the construction waste, such as mud, gypsum, etc., cannot be used as aggregates, and these components have a smaller hardness. When the construction waste is crushed into smaller particles, it is easier to form particles or dust smaller than the original aggregate in the construction waste and can be separated by a vibrating screen. However, the garbage recycling fragments obtained by crushing the construction waste by the pulverizer still have smaller hardness components such as mud and gypsum with a diameter of 1mm-3mm. At this time, the garbage recycling fragments obtained also contain a considerable amount of metal. Most of these metals are ferrous metals, mostly from the steel bars in concrete. When there are ferrous metal fragments in concrete functional components, it is not conducive to resisting water erosion, especially seawater erosion. Therefore, the ferrous metal blocks in the garbage recycling fragments should be removed by magnetic screening. The ferrous metal fragments (or magnetic metal fragments) separated by the magnetic screen are also conducive to metal recovery and reuse, reducing the overall cost of construction waste recovery and reuse, and improving the economic benefits of construction waste reuse. However, the primary recycled garbage fragments obtained after magnetic separation still contain fragments with lower hardness such as mud and gypsum.
[0024] In order to further separate the components with lower hardness such as mud and gypsum in the primary recycled garbage fragments, the primary recycled garbage fragments need to be further processed. The primary recycled garbage fragments can be first placed in a container, then soaked in water for at least 1 hour, and then the soaked primary recycled garbage fragments are placed in a blender (or the primary recycled garbage fragments are directly placed in a blender and then soaked in water for at least 1 hour) to soften the mud and gypsum in the primary recycled garbage fragments, and then a vertical downward pressure of appropriate size and horizontal stirring are continuously applied directly to the top of the soaked primary recycled garbage fragments in the blender. After the blender horizontally stirs and soaks the primary recycled garbage fragments for at least 5 minutes, the primary recycled garbage fragments can be poured onto a 7-mesh screen (or a 16-mesh screen, the number of meshes of the screen is determined according to the diameter of the primary recycled garbage fragments crushed and screened by the crusher) for water washing to clean the primary recycled garbage fragments and remove the ground mud and gypsum blocks and other components with lower hardness, thereby obtaining secondary recycled garbage fragments. It can be understood that the purpose of continuously applying pressure on the upper part of the primary recycled garbage fragments in the mixer is to prevent the upper layer of the primary recycled garbage fragments in the mixer from being stirred by the mixer, rather than to compact the primary recycled garbage fragments in the mixer. Therefore, the pressure continuously applied on the upper part of the primary recycled garbage fragments in the mixer should not be greater than the buoyancy of the water on the upper layer of the primary recycled garbage fragments in the mixer. It can be understood that horizontally stirring the water-immersed primary recycled garbage fragments can make the primary recycled garbage fragments at different heights to be ground in layers as much as possible, avoid vertical transportation of the primary recycled garbage fragments, and reduce the energy consumption of the mixer.
[0025] As shown in the attached picture Figure 2As shown, after the primary recycled garbage fragments are stirred, they are preferably placed on a screen with a slightly larger mesh number, for example, a 7-mesh screen (or a 16-mesh screen, the mesh holes should be slightly smaller than the diameter of the primary recycled garbage fragments) for washing to obtain secondary recycled garbage fragments. The main reason for using a screen with a slightly larger mesh number for washing is that after the primary recycled garbage fragments are stirred, the aggregate blocks with a larger hardness may also become slightly smaller in diameter due to the grinding between the primary recycled garbage fragments. The primary recycled garbage fragments are directly and continuously pressed vertically downward instead of continuously pressing the water surface downward, so as to ensure that the mixer can stir the primary recycled garbage fragments in the entire mixer including the primary recycled garbage fragments on the upper layer of the mixer when stirring the primary recycled garbage fragments. The advantages of soaking the primary recycled garbage fragments in water first and then continuously pressurizing and stirring the primary recycled garbage fragments are as follows: First, the components with lower hardness, such as mud and gypsum, are soaked and softened first, and then stirred in a mixer, so that the mud and gypsum blocks are easier to be ground into smaller fragments, while the size of particles with higher hardness, such as stone, gravel and broken bricks, will not be greatly affected. At the same time, soaking also helps to separate additives such as resin attached to the surface of aggregate from the aggregate, so that the additives attached to the surface of aggregate are easier to remove through the subsequent stirring and grinding action. Secondly, when the mixer stirs the primary recycled garbage fragments, the stirring blades of the mixer will generate a lot of heat. If there is no heat conduction from water, the local area in the mixer will overheat, causing the stirring blades of the mixer to soften. Water immersion stirring can speed up the heat transfer in the mixer, effectively prevent local overheating and deformation of the mixer blades, and ensure that the primary recycled garbage fragments are easier to be stirred and driven, so that the primary recycled garbage fragments are effectively ground when being stirred and the mud and gypsum blocks with lower hardness are easier to be ground and removed. Thirdly, when the mixer stirs the primary recycled waste fragments, the water immersion can also utilize the buoyancy of water to make the primary recycled waste fragments in the mixer easier to stir and ensure that the primary recycled waste fragments at the bottom of the mixer can also move under the drive of the mixer's stirring blades and produce grinding between the primary recycled waste fragments at the bottom of the mixer. Finally, the water immersion stirring of the primary recycled waste fragments can also make the primary recycled waste fragments after stirring be washed more cleanly, preventing dust from adhering to the surface of the primary recycled waste fragments and affecting the molding and strength of the functional components prepared later.
[0026] It is worth noting that the construction waste or building waste in this article is broken into pieces with a diameter of 1-3mm, which is convenient for the mixer to stir and form an effective grinding effect between the primary recycling garbage pieces. When the diameter of the primary recycling garbage pieces is larger, not only is it difficult for the mixer to stir directly such a large primary recycling garbage pieces, but the grinding effect between the primary recycling garbage pieces is also poor. However, if the construction waste is broken into pieces with a smaller diameter (for example, a diameter less than 1mm), although the diameter of the primary recycling garbage pieces is smaller and it is easier to remove the smaller hardness components such as mud and gypsum, the diameter of the primary recycling garbage pieces is too small, which will not only lead to higher energy consumption during the crushing of the early crusher, but also cause the primary aggregate recovery rate in the construction waste to be significantly reduced. In addition, the diameter of the primary recycling garbage pieces obtained by the early crusher crushing and magnetic sieve is too small, which also leads to a smaller processing redundancy when leaving for further processing of the recycled aggregate in the later stage, which is not conducive to the later processing of the recycled aggregate as needed and obtaining the aggregate of the appropriate diameter. Furthermore, in order to ensure that the primary recycled garbage fragments in the mixer can be fully stirred, a high-pressure water flow can be continuously introduced from the bottom of the mixer from bottom to top. The high-pressure water flow in this article refers to a water flow with a water pressure of 0.6MPa-1.5MPa. If the water pressure is too low, it will not be able to provide pressure from the bottom to ensure that the primary recycled garbage fragments are subjected to sufficient upward force, but if the pressure is too high, it may cause damage to the mixer or the water supply pipe. Before the stirring begins, the high-pressure water flow must be introduced first, and then pressed on the top of the primary recycled garbage fragments in the mixer through a perforated pressure plate, and finally the stirring begins. It can be understood that the water flow can overflow from the through-holes of the perforated pressure plate and flow out through the overflow hole on the mixer. Correspondingly, after the high-pressure water flow is introduced, it continuously applies an upward force to the primary recycled garbage fragments in the mixer, so that the stirring blades can easily drive the primary recycled garbage fragments in the mixer. When the water flow continuously overflows and flows away during the stirring process, it can also wash away the lighter impurities in the primary recycled garbage fragments, such as resin (the fragments with higher hardness in the primary recycled garbage fragments also have a higher density and are not easy to be washed away), thereby improving the purity of the primary recycled garbage fragments. In addition, the water flow can also take away the mud and debris produced after the components with lower hardness, such as mud and gypsum, are crushed. Furthermore, the high-pressure water flow is provided to the primary recycled garbage fragments in the mixer through the water balancing plate arranged at the bottom of the mixer, so that the primary recycled garbage in the mixer is evenly stressed and fully stirred.
[0027] According to the embodiment of the present invention, the secondary recycled garbage fragments obtained after stirring and rinsing by the mixer contain very few impurity components with smaller hardness, such as mud and gypsum, and the diameter size does not change much compared with the primary recycled garbage fragments, but is more uniform. In order to further improve the quality of the secondary recycled garbage fragments and remove the impurity components with smaller hardness, such as mud and gypsum, contained in the secondary recycled garbage fragments, the secondary recycled garbage fragments can be further processed. The processing and impurity removal methods for the secondary recycled garbage fragments are mainly grinding and screening. Generally, the secondary recycled garbage fragments are ground by a ball mill. As shown in the attached figure Figure 2 and Figure 3 As shown in the figure, when the secondary recycled garbage fragments are ground into particles with a particle size of 1.18 mm (when the particle size of the primary recycled garbage fragments is 1 mm, no further grinding is required), 0.63 mm, 0.315 mm and 0.16 mm (or less than 0.16 mm), after detecting the diffraction intensity, it is found that among the various particle size components, the diffraction intensity of SiO2 is not much different, and the diffraction intensity of CaCO3 increases with the decrease of the particle size, and when the particle size is 0.16 mm (or less than 0.16 mm), the CaSO4·2H2O diffraction peak appears. Therefore, grinding the secondary recycled garbage fragments into particles with a particle size of 0.16 mm not only helps to remove impurity components with smaller hardness such as mud and gypsum, but also helps to remove moisture in the secondary recycled garbage fragments to obtain purer fine aggregate. In this article, in order to ensure the grinding and impurity removal effect of the ball mill, it is preferred to control the ball mill to grind the secondary recycled garbage fragments into garbage recycled fragments with a particle size of 0.16mm (the particle size of fine aggregate is 0.15-5.0mm), and after grinding for at least 30 minutes, the recycled regenerated primary aggregate coarse material is obtained, and then the recycled regenerated primary aggregate coarse material is vibrated through a 100-mesh vibrating screen (aperture is about 0.15mm) to remove fine dust, and obtain the recycled regenerated primary aggregate of the present invention. It can be understood that the fine dust removed by the vibrating screen contains a considerable amount of impurity components with relatively small hardness such as mud and gypsum. The total content of SiO2, Al2O3, Fe2O3 and CaO in the recycled primary aggregate obtained by the present invention after screening and removing fine dust by a vibrating screen is 83.97%-92.67%, the micro powder content is ≤3.0%, the firmness is ≤10.0%, the single-stage maximum crushing value is ≤25%, and the apparent density is ≥2350kg / m 3 , bulk density ≧1300kg / m 3 , in line with national quality standards for fine aggregate.
[0028] According to an embodiment of the present invention, in order to improve the grinding effect, a grinding aid can be added when grinding the secondary recycled garbage fragments. The grinding aid used to improve the grinding effect of the present invention is a liquid (solution or suspended liquid), which is added drop by drop when the ball mill grinds the secondary recycled garbage fragments, so that the ball mill can fully and evenly grind the secondary recycled garbage fragments to obtain recycled regenerable raw aggregate coarse material. The grinding aid used to improve the grinding effect of the present invention contains water, glycerol, tert-butyl diethanolamine, ethylene glycol, diethanolamine, sodium nitrite, calcium nitrite and calcium chloride, wherein glycerol has the effect of antifreeze and preventing steel corrosion while increasing fluidity, and tert-butyl diethanolamine, ethylene glycol and diethanolamine have an antifreeze effect while effectively reducing the charge density in the grinding process and improving the grinding efficiency. It is noteworthy that the active ingredients of the grinding aid for improving the grinding effect of the present invention all have antifreeze effect, so that the liquid phase concentration of concrete can be significantly changed at low temperature (referring to below zero degrees), the freezing point is reduced, and the liquid phase of concrete is guaranteed to exist at low temperature, the amount of ice in the concrete is reduced, and the ice crystal size is made fine and uniformly dispersed, thereby reducing the destructive stress to the concrete. In addition, ethylene glycol and diethanolamine are diols and diolamines, respectively, and the chain length is shorter, and tert-butyl diethanolamine is diolamine, and the chain length is longer, so that tert-butyl diethanolamine, ethylene glycol and diethanolamine form complementary synergistic effects, which can not only significantly reduce the amount of ethylene glycol and diethanolamine required when preparing concrete components and improve the compressive strength of concrete, and ensure that the compressive strength of concrete can remain stable. Finally, all active ingredients of the grinding aid for improving the grinding effect of the present invention all have good water solubility and have antifreeze effect, which can ensure that each component can be uniformly dispersed during the grinding process, and can significantly improve the antifreeze performance of concrete. In other words, the recycled raw aggregate obtained by recycling the aggregate in the construction waste according to the embodiment of the present invention can not only prevent freezing, but also significantly improve the strength of the prepared recycled raw aggregate and ensure the uniform quality of the recycled raw aggregate. Specifically, the weight ratio of the grinding aid used to improve the grinding effect of the present invention to the secondary recycled garbage fragments is (1-1.5):100, and the grinding aid includes 55-60 weight units of water, 8-10 weight units of glycerol, 10-12 weight units of tert-butyl diethanolamine, 5-6 weight units of ethylene glycol, 6-8 weight units of diethanolamine, 2-4 weight units of sodium nitrite, 3-4.5 weight units of calcium nitrite and 3-4.5 weight units of calcium chloride.
[0029] The preparation example of recycled regenerated primary aggregate of the present invention is as follows:
[0030] Example 1:
[0031] First, prepare recycled and renewable virgin aggregate: first, mix 60 weight units of water, 8 weight units of glycerol, 10 weight units of tert-butyl diethanolamine, 5 weight units of ethylene glycol, 6 weight units of diethanolamine, 2 weight units of sodium nitrite, 3 weight units of calcium nitrite and 3 weight units of calcium chloride to prepare a grinding aid, and then take 1 weight unit of the grinding aid and mix and grind with 100 weight units of secondary recycled garbage fragments to prepare recycled and renewable virgin aggregate.
[0032] Then, prepare 2 weight units of P.O42.5 cement, 5.6 weight units of coarse aggregate, 2.8 weight units of recycled primary aggregate (particle size not more than 0.16 mm), 0.15 weight unit of basalt fiber (diameter 12 μm, length 6 mm), 0.5 weight unit of silica, 0.3 weight unit of calcium carbonate, 0.3 weight unit of epoxy resin, 0.8 weight unit of water and 0.25 weight unit of modifier, wherein the cement, silica, calcium carbonate and epoxy resin all meet the nanometer standard and are stirred in a base material mixer for at least 5 minutes, and then the stirred base material is put into a molding machine to prepare a cubic specimen with a side length of 150 mm as a standard size specimen for the compressive strength of concrete.
[0033] Example 2:
[0034] First, prepare recycled and renewable virgin aggregate: first, mix 60 weight units of water, 8 weight units of glycerol, 10 weight units of tert-butyl diethanolamine, 5 weight units of ethylene glycol, 6 weight units of diethanolamine, 2 weight units of sodium nitrite, 3 weight units of calcium nitrite and 3 weight units of calcium chloride to prepare a grinding aid, and then take 1 weight unit of the grinding aid and mix and grind with 100 weight units of secondary recycled garbage fragments to prepare recycled and renewable virgin aggregate.
[0035] Then, prepare 5 weight units of P.O42.5 cement, 24 weight units of coarse aggregate, 7 weight units of recycled primary aggregate (particle size not more than 0.16 mm), 0.3 weight units of basalt fiber (diameter 12 μm, length 6 mm), 3 weight units of silica, 0.5 weight units of calcium carbonate, 0.8 weight units of epoxy resin, 3.0 weight units of water and 0.25 weight units of modifier, wherein the cement, silica, calcium carbonate and epoxy resin all meet the nanoscale standard, put them into a base material mixer and stir them in the base material mixer for at least 5 minutes, and then put the stirred base material into a molding machine to form a cubic specimen with a side length of 150 mm as a standard size specimen for the compressive strength of concrete.
[0036] Example 3:
[0037] First, prepare recycled and renewable virgin aggregate: first, 55 weight units of water, 10 weight units of glycerol, 12 weight units of tert-butyl diethanolamine, 6 weight units of ethylene glycol, 8 weight units of diethanolamine, 4 weight units of sodium nitrite, 4.5 weight units of calcium nitrite and 4.5 weight units of calcium chloride are mixed evenly to prepare a grinding aid, and then 1 weight unit of the grinding aid is mixed and ground with 100 weight units of secondary recycled garbage fragments to prepare recycled and renewable virgin aggregate.
[0038] Then, prepare 2 weight units of P.O42.5 cement, 5.6 weight units of coarse aggregate, 2.8 weight units of recycled primary aggregate (particle size not more than 0.16 mm), 0.15 weight unit of basalt fiber (diameter 12 μm, length 6 mm), 0.5 weight unit of silica, 0.3 weight unit of calcium carbonate, 0.3 weight unit of epoxy resin, 0.8 weight unit of water and 0.25 weight unit of modifier, wherein the cement, silica, calcium carbonate and epoxy resin all meet the nanometer standard and are stirred in a base material mixer for at least 5 minutes, and then the stirred base material is put into a molding machine to prepare a cubic specimen with a side length of 150 mm as a standard size specimen for the compressive strength of concrete.
[0039] Example 4:
[0040] First, prepare recycled and renewable virgin aggregate: first, 55 weight units of water, 10 weight units of glycerol, 12 weight units of tert-butyl diethanolamine, 6 weight units of ethylene glycol, 8 weight units of diethanolamine, 4 weight units of sodium nitrite, 4.5 weight units of calcium nitrite and 4.5 weight units of calcium chloride are mixed evenly to prepare a grinding aid, and then 1 weight unit of the grinding aid is mixed and ground with 100 weight units of secondary recycled garbage fragments to prepare recycled and renewable virgin aggregate.
[0041] Then, prepare 5 weight units of P.O42.5 cement, 24 weight units of coarse aggregate, 7 weight units of recycled primary aggregate (particle size not more than 0.16 mm), 0.3 weight units of basalt fiber (diameter 12 μm, length 6 mm), 3 weight units of silica, 0.5 weight units of calcium carbonate, 0.8 weight units of epoxy resin, 3.0 weight units of water and 0.25 weight units of modifier, wherein the cement, silica, calcium carbonate and epoxy resin all meet the nanoscale standard, put them into a base material mixer and stir them in the base material mixer for at least 5 minutes, and then put the stirred base material into a molding machine to form a cubic specimen with a side length of 150 mm as a standard size specimen for the compressive strength of concrete.
[0042] Example 5:
[0043] First, prepare recycled and renewable virgin aggregate: first, evenly mix 58 weight units of water, 9 weight units of glycerol, 11 weight units of tert-butyl diethanolamine, 5 weight units of ethylene glycol, 7 weight units of diethanolamine, 3 weight units of sodium nitrite, 4 weight units of calcium nitrite and 4 weight units of calcium chloride to prepare a grinding aid, and then take 1 weight unit of the grinding aid and mix and grind with 100 weight units of secondary recycled garbage fragments to prepare recycled and renewable virgin aggregate.
[0044] Then, prepare 3 weight units of P.O42.5 cement, 4.8 weight units of coarse aggregate, 5 weight units of recycled primary aggregate (particle size not more than 0.16 mm), 0.1 weight unit of basalt fiber (diameter 10 μm, length 15 mm), 1 weight unit of silica, 0.6 weight unit of calcium carbonate, 0.4 weight unit of epoxy resin, 1.6 weight unit of water and 0.35 weight unit of modifier, wherein the cement, silica, calcium carbonate and epoxy resin all meet the nanometer standard and are stirred in a base material mixer for at least 5 minutes, and then the stirred base material is put into a molding machine to prepare a cubic specimen with a side length of 150 mm as a standard size specimen for the compressive strength of concrete.
[0045] Example 6:
[0046] First, prepare recycled and renewable virgin aggregate: first, evenly mix 58 weight units of water, 9 weight units of glycerol, 11 weight units of tert-butyl diethanolamine, 5 weight units of ethylene glycol, 7 weight units of diethanolamine, 3 weight units of sodium nitrite, 4 weight units of calcium nitrite and 4 weight units of calcium chloride to prepare a grinding aid, and then take 1 weight unit of the grinding aid and mix and grind with 100 weight units of secondary recycled garbage fragments to prepare recycled and renewable virgin aggregate.
[0047] Then, prepare 4.5 weight units of P.O42.5 cement, 18 weight units of coarse aggregate, 6 weight units of recycled primary aggregate (particle size not more than 0.16 mm), 0.3 weight unit of basalt fiber (diameter 20 μm, length 30 mm), 2 weight units of silica, 0.45 weight unit of calcium carbonate, 0.7 weight unit of epoxy resin, 2.8 weight unit of water and 0.4 weight unit of modifier, wherein the cement, silica, calcium carbonate and epoxy resin all meet the nanoscale standard, put them into a base material mixer and stir them in the base material mixer for at least 5 minutes, and then put the stirred base material into a molding machine to form a cubic specimen with a side length of 150 mm as a standard size specimen for the compressive strength of concrete.
[0048] In order to determine the quality of the recycled primary aggregate of the present invention, the present invention further provides a comparative example of a standard size test piece with a side length of 150 mm prepared using primary fine aggregate (natural sand) as the fine aggregate raw material as follows:
[0049] Comparative Example 1:
[0050] Prepare 2 weight units of P.O42.5 cement, 5.6 weight units of coarse aggregate, 2.8 weight units of primary fine aggregate (particle size not greater than 0.16 mm), 0.15 weight unit of basalt fiber (diameter 12 μm, length 6 mm), 0.5 weight unit of silica, 0.3 weight unit of calcium carbonate, 0.3 weight unit of epoxy resin, 0.8 weight unit of water and 0.25 weight unit of modifier, wherein the cement, silica, calcium carbonate and epoxy resin all meet the nanometer standard and are stirred in a base material mixer for at least 5 minutes, and then the stirred base material is put into a molding machine for molding, and under the same conditions and environment, a cubic specimen with a side length of 150 mm is prepared as a standard size specimen of concrete compressive strength.
[0051] Comparative Example 2:
[0052] Prepare 2 weight units of P.O42.5 cement, 5.6 weight units of coarse aggregate, 2.8 weight units of primary fine aggregate (particle size not greater than 0.16 mm), 0.15 weight unit of basalt fiber (diameter 12 μm, length 6 mm), 0.5 weight unit of silica, 0.3 weight unit of calcium carbonate, 0.3 weight unit of epoxy resin, 0.8 weight unit of water and 0.25 weight unit of modifier, wherein the cement, silica, calcium carbonate and epoxy resin all meet the nanometer standard and are stirred in a base material mixer for at least 5 minutes, and then the stirred base material is put into a molding machine for molding, and under the same conditions and environment, a cubic specimen with a side length of 150 mm is prepared as a standard size specimen of concrete compressive strength.
[0053] Comparative Example 3:
[0054] Prepare 3 weight units of P.O42.5 cement, 4.8 weight units of coarse aggregate, 5 weight units of primary fine aggregate (particle size not greater than 0.16 mm), 0.1 weight unit of basalt fiber (diameter 10 μm, length 15 mm), 1 weight unit of silica, 0.6 weight unit of calcium carbonate, 0.4 weight unit of epoxy resin, 1.6 weight unit of water and 0.35 weight unit of modifier, wherein the cement, silica, calcium carbonate and epoxy resin all meet the nanometer standard and are stirred in a base material mixer for at least 5 minutes, and then the stirred base material is put into a molding machine for molding, and under the same conditions and environment, a cubic specimen with a side length of 150 mm is prepared as a standard size specimen of concrete compressive strength.
[0055] Comparative Example 4:
[0056] Prepare 4.5 weight units of P.O42.5 cement, 18 weight units of coarse aggregate, 6 weight units of primary fine aggregate (particle size not greater than 0.16 mm), 0.3 weight unit of basalt fiber (diameter 20 μm, length 30 mm), 2 weight units of silica, 0.45 weight unit of calcium carbonate, 0.7 weight unit of epoxy resin, 2.8 weight unit of water and 0.4 weight unit of modifier, wherein the cement, silica, calcium carbonate and epoxy resin all meet the nanoscale standard, put them into a base material mixer and stir them in the base material mixer for at least 5 minutes, then put the stirred base material into a molding machine for molding, and prepare a cubic specimen with a side length of 150 mm under the same conditions and environment as a standard size specimen of concrete compressive strength.
[0057] It can be understood that in order to ensure that the performance of the standard-sized test pieces prepared in the above examples and comparative examples is not affected by the external environment, the steps in the above examples and comparative examples are all carried out under the same conditions (or substantially the same conditions). The same or equivalent conditions herein refer to the same or substantially the same temperature, humidity, coagulation time, storage location, and equipment conditions.
[0058] According to CECS13:2009 "Fiber Concrete Test Method Standard", a drop hammer impact test was performed on the prepared standard size specimens using a drop hammer impact instrument, and the compressive strength and flexural strength of the standard size specimens prepared in each example and comparative example were calculated. The test results are shown in Table 1:
[0059] Table 1: Compressive strength and flexural strength tests of standard size specimens
[0060]
[0061]
[0062] SPSS18 analysis software tested the significant difference between the compressive strength and flexural strength of standard size specimens in the example group and the comparison group, and the results showed that there was no significant difference between the two groups.
[0063] Furthermore, according to GB / T 50082-2009 concrete freeze-thaw cycle test method standard, the number of freeze-thaw cycles of the standard-sized specimens prepared in each example and comparative example was tested. The freeze-thaw cycle test method of the standard-sized specimens was the quick freezing method:
[0064] The prepared standard size specimens are grouped into 3 pieces and the curing is completed according to the curing age. 4 days before the freeze-thaw test, the specimens are taken out from the curing point and soaked in (20±2)℃ water for 4 days. After the test age, the specimens are taken out in time, the surface moisture is wiped with a wet cloth, the appearance dimensions are measured, and the specimens are numbered, the initial mass is weighed, and the initial value of the transverse fundamental frequency is determined. The test specimens are placed in the specimen box as required, and the time and the specimen rack are placed in the freeze-thaw box. Clean water is injected into the specimen box, and it is ensured that the water level meets the requirements during the entire test. Each freeze-thaw cycle should be completed within 2h to 4h, and the melting time and temperature change of the specimens should meet the requirements. The conversion time between freezing and melting should not exceed 10min. Every 25 freeze-thaw cycles, the transverse fundamental frequency of the specimen is measured according to the standard method. After the measurement, the specimen is quickly turned around and reloaded into the specimen box, clean water is added to continue the test. The test can be ended when a condition that meets the conditions occurs. The test results are as shown in Table 2:
[0065] Table 2: Test of freeze-thaw cycle times of standard size specimens
[0066]
[0067]
[0068] SPSS18 analysis software tested the significant difference between the number of freeze-thaw cycles of standard-sized specimens in the example group and the comparison group, and the results showed that there was no significant difference between the two groups.
[0069] Furthermore, the sulfate corrosion resistance of the standard-sized specimens prepared in each example and comparative example was tested. The specific testing method is as follows:
[0070] 1. Take the specimens that need to undergo dry-wet cycles out of the standard curing room 2 days before the 28-day curing period. Wipe the surface moisture off the specimens, then put the specimens into the oven and bake them at (80±5) degrees Celsius for 48 hours. After drying, cool the specimens to room temperature in a dry environment.
[0071] 2. After the specimens are dried and cooled, they should be immediately placed in the specimen box (rack). A distance of 20 mm should be maintained between adjacent specimens, and the distance between the specimens and the side wall of the specimen box should not be less than 20 mm.
[0072] 3. After the specimen is placed in the specimen box, the prepared 5% Na2SO4 solution should be placed in the specimen box, and the solution should at least exceed the surface of the uppermost specimen by 20mm. Then start soaking. The time from the beginning of the specimen being placed in the solution to the end of the soaking process should be (15±0.5)h. The time for injecting the solution should not exceed 30min. The soaking age is counted from the time the concrete specimen is moved into the 5% Na2SO4 solution.
[0073] During the experiment, the pH value of the solution should be checked and adjusted regularly. The pH value of the solution can be tested every 15 cycles, and the pH value of the solution should always be maintained between 6 and 8. The temperature of the solution should be controlled at (25-30) degrees Celsius. It is also possible not to test its pH value, but the experimental solution should be replaced once a month.
[0074] 4. After the immersion process is completed, drain the liquid immediately and drain the solution within 30 minutes. After the solution is drained, the specimen should be air-dried for 30 minutes. The time from the beginning of the solution draining to the air-drying of the specimen should be 1 hour.
[0075] 5. After the air-drying process is completed, the temperature in the specimen box should be raised to 80 degrees Celsius immediately to start drying. The heating process should be completed within 30 minutes. After the temperature reaches 80 degrees Celsius, the temperature should be maintained at (80±5) degrees Celsius. The time from the start of heating to the start of cooling should be 6 hours.
[0076] 6. After the drying process is completed, the specimen is cooled immediately. The time from the beginning of cooling to the cooling of the specimen surface temperature in the specimen box to (25-30) degrees Celsius is 2 hours.
[0077] 7. The total time of each dry-wet cycle should be (24±2)h. Then, add the solution again and follow the steps 3 to 6 above to perform the next dry cycle.
[0078] 8. After reaching the number of dry cycles specified in Table 14.0.2 (see Table 1) of the Standard Specification for Test Methods for Long-term Performance and Durability of Ordinary Concrete, the compressive strength test should be carried out in a timely manner. At the same time, observe the damage of the concrete surface after the dry cycle and describe the appearance. When the specimen has serious peeling, corner loss and other defects, first use high-strength gypsum to fill it and then carry out the compressive strength test.
[0079] 9. When one of the following three situations occurs during the dry-wet cycle experiment, stop the experiment:
[0080] 1) When the compressive strength and corrosion resistance coefficient reaches 75%;
[0081] 2) The number of dry cycles reaches 150 times;
[0082] 3) The number of dry-wet cycles corresponding to the designed sulfate resistance grade
[0083] 10. The comparison specimens shall continue to maintain the original curing conditions until the dry cycle is completed, and then the compressive strength test shall be carried out simultaneously with the original specimens of the dry-wet cycle test. The sulfate resistance grade shall be determined by the maximum number of dry-wet cycles when the compressive strength corrosion resistance coefficient of the specimen drops to not less than 75%. The compressive strength corrosion resistance coefficient of concrete shall be calculated according to the following formula: K f =(F cn / Fc0 )×100%, the test results are as shown in Table 3:
[0084] Table 3: Test of the number of cycles of sulfate corrosion resistance of standard size specimens
[0085] Serial number Cycle times Example 1 151 Example 2 168 Example 3 175 Example 4 180 Example 5 163 Example 6 165 Comparative Example 1 164 Comparative Example 2 177 Comparative Example 3 177 Comparative Example 4 203
[0086] SPSS18 analysis software tested the significant difference between the number of sulfate corrosion resistance cycles of standard-sized specimens in the example group and the comparative group, and the results showed that there was no significant difference between the two groups.
[0087] In summary, the standard-sized specimens obtained by the preparation method of an embodiment of the present invention have a 28d compressive strength ≥ 86 MPa, a 28d flexural strength ≥ 11.8 MPa, a freeze-thaw cycle number ≥ 180 times, a sulfate erosion cycle number ≥ 151 times, and excellent performance, and can be used to prepare structural parts such as anti-erosion regeneration functional components for embankment protection.
[0088] According to an embodiment of the present invention, the method for recycling raw aggregates using solid construction waste comprises the following steps:
[0089] Step 1: Crush the solid construction waste into recycling fragments with a diameter of 1mm-3mm, and separate them through a 6-15 mesh sieve;
[0090] Step 2: Using a magnetic screen to remove the iron-containing metal pieces in the garbage recycling fragments to obtain primary recycling garbage fragments;
[0091] Step 3: Soak the primary recycling waste fragments in water for at least 1 hour;
[0092] Step 4: Soak the soaked primary recycling waste pieces in water and stir for at least 5 minutes;
[0093] Step 5: pouring the fully stirred primary recycled garbage fragments onto a 7-16 mesh screen and washing them with water to obtain secondary recycled garbage fragments; and
[0094] Step 6: Grind the secondary recycled garbage fragments to grind them into aggregate particles with a particle size of 0.16 mm, and screen the ground aggregate particles through a 100-mesh vibrating screen to obtain recycled and regenerated primary aggregate.
[0095] Preferably, step 4 comprises the following steps:
[0096] Step 4.1: first, vertically downward pressure is continuously applied to the upper part of the primary recycled waste fragments soaked in the mixer, and water flow with a water pressure of 0.6MPa-1.5MPa is continuously introduced from bottom to top below the primary recycled waste fragments soaked in the mixer, wherein the vertically downward pressure is not greater than the buoyancy of the water on the primary recycled waste fragments in the upper layer of the mixer; and
[0097] Step 4.2: Then, the soaked primary recycled waste pieces are stirred horizontally under water immersion conditions for at least 5 minutes.
[0098] Those skilled in the art should understand that the embodiments of the present invention described above and shown in the accompanying drawings are only for illustrative purposes and are not intended to limit the present invention.
[0099] The purpose of the present invention has been completely and effectively achieved. The functional and structural principles of the present invention have been demonstrated and explained in the embodiments, and the embodiments of the present invention may be deformed or modified in any way without departing from the principles.
Claims
1. A method for recycling raw aggregates from solid construction waste, comprising the following steps: Step 1: Crush the solid construction waste into recycling fragments with a diameter of 1mm-3mm, and separate them through a 6-15 mesh sieve; Step 2: Using a magnetic screen to remove the iron-containing metal pieces in the garbage recycling fragments to obtain primary recycling garbage fragments; Step 3: Soak the primary recycling waste pieces in water for at least 1 hour; Step 4: Soak the soaked primary recycling waste pieces in water and stir for at least 5 minutes; Step 5: Pour the fully stirred primary recycled garbage fragments onto a 7-16 mesh sieve and wash with water to obtain secondary recycled garbage fragments; and Step 6: Grind the secondary recycled waste fragments to grind them into aggregate particles with a particle size of 0.16 mm, and screen the ground aggregate particles through a 100-mesh vibrating screen to obtain recycled and regenerated primary aggregate, wherein the solid construction waste comes from the walls of the building.
2. The method for recycling primary aggregates from solid construction waste according to claim 1, characterized in that: The step 4 comprises the following steps: Step 4.1: first, vertically downward pressure is continuously applied to the upper part of the primary recycled waste fragments soaked in the mixer, and water flow with a water pressure of 0.6MPa-1.5MPa is continuously introduced from bottom to top below the primary recycled waste fragments soaked in the mixer, wherein the vertically downward pressure is not greater than the buoyancy of the water on the primary recycled waste fragments in the upper layer of the mixer; and Step 4.2: Then, the soaked primary recycled waste pieces are stirred horizontally under water immersion conditions for at least 5 minutes.
3. The method for recycling primary aggregates from solid construction waste according to claim 2, characterized in that: Water flow is provided to the primary recycled garbage fragments in the mixer through a water distribution plate arranged at the bottom of the mixer.
4. The method for recycling primary aggregates from solid construction waste according to claim 3, characterized in that: When grinding the secondary recycled garbage fragments, the grinding aid is added dropwise in a ratio of (1-1.5) to the weight ratio of the grinding aid to the secondary recycled garbage fragments: 100, wherein the grinding aid contains 55-60 weight units of water, 8-10 weight units of glycerol, 10-12 weight units of tert-butyl diethanolamine, 5-6 weight units of ethylene glycol, 6-8 weight units of diethanolamine, 2-4 weight units of sodium nitrite, 3-4.5 weight units of calcium nitrite and 3-4.5 weight units of calcium chloride.
5. The method for recycling primary aggregates from solid construction waste according to claim 4, characterized in that: The grinding aid contains 55 weight units of water, 10 weight units of glycerol, 12 weight units of tert-butyldiethanolamine, 6 weight units of ethylene glycol, 8 weight units of diethanolamine, 4 weight units of sodium nitrite, 4.5 weight units of calcium nitrite and 4.5 weight units of calcium chloride.
6. The method for recycling primary aggregates from solid construction waste according to claim 4, characterized in that: The grinding aid contains 60 weight units of water, 8 weight units of glycerol, 10 weight units of tert-butyldiethanolamine, 5 weight units of ethylene glycol, 6 weight units of diethanolamine, 2 weight units of sodium nitrite, 3 weight units of calcium nitrite and 3 weight units of calcium chloride.